Strategi Bersaing Unit Pemasaran Dalam Meningkatkan Penyaluran Produk Kredit Usaha Rakyat Bagi Pelaku Umkm Pada PT. BNI Cab. Selatpanjang - Bestari, Juliano; Turay, Tiara (CV. ITTC INDONESIA, 2025)
Bank BNI Selat Panjang branch as a banking service certainly has several obstacles in distributing financing products to the community, one of these financing products is the People's Business Credit (KUR). Some of these obstacles include access to capital for MSMEs, remapping of branch credit processes, changes in KUR distribution provisions and land problems in the Regency. Kep. Meranti - Selatpanjang. Bank BNI as one of the largest banks in Indonesia has an important role in helping MSMEs gain access to capital through its credit products. Therefore, the purpose of this study is to find out (1) to find out the competitive strategy of the Marketing Unit of PT. BNI in increasing the distribution of People's Business Credit for MSMEs at PT. BNI Selatpanjang Branch. (2) To find out the obstacles faced by the Marketing Unit of PT. BNI in creating a competitive strategy in marketing People's Business Credit Products for MSMEs at PT. BNI Selatpanjang Branch. The research method used is qualitative descriptive research with the type of field research where the research is conducted using the method of collecting data directly at the location where the research was conducted. The results of the study found that the strength of Bank BNI Selatpanjang branch is currently High (Criteria value 4) in the sense that Bank BNI Selatpanjang branch is able to compete with other competitors. In terms of opportunities, Bank BNI Selatpnjang has criteria 3 / moderate. So there needs to be a re-evaluation of the performance results that have been carried out in order to create better opportunities in the future. Total score of Strength (S) - total score of Opportunities (O) = 21.156- 34.2779 = -13.12 and calculation for W-O: Total score of Weakness (W) - total score of Opportunities (O) = 73.512 - 95.14802 = -21.63 Calculation for S-T: Total score of Strength (S) - total score of Treaths (T) = 21.156 - 95.14802 = -. 73.99 then, calculation for W-T, then Total score of Weakness (W) - total score of Treaths (T) = 73.512 - 95.14802 = -21.63. from these results it can be concluded that PT. Bank BNI Selatpanjang branch is currently carrying out a defense strategy that is being used in competing with other competitors to market KUR products for MSME